KAJIAN KRITIS BEBERAPA PASAL DALAM UNDANG-UNDANG NOMOR 13 TAHUN 2003 TENTANG KETENAGAKERJAAN - Abdul Rokhim (Institute for Research and Community Services (LPPM) of Wijaya Kusuma Surabaya University, 2007)
Role of labour in filling national development very big its meaning. Attention to prosperity of labour shall be conducted seriously because related the mentioned sliver with effort improve national productivity. For the reason protection of law to labour have to be balanced with protection of law which have been specified to employer party. Difference of social status among activity energy labour with employer oftentimes problems menyulut that happened To employer party which is strong social status of often in specifying policy cause loss to labour. On the other side labour party is not easy to present to which its it, considering its much more compared to low social status of its employer Even what conducted by employer frequently get out of responsibility judicially The mentioned happened because rule which included in of No. 13 Year 2003 about conducive Ketenagakeejaan for that and still there are congeniality difference so that emerge other interpretation.